Kandungan Tembaga (Cu) dan Timbal (Pb) pada Lamun Enhalus accoroides dari Perairan Batam, Kepulauan Riau, Indonesia - Ismarti Ismarti; Ramses Ramses; Fitrah Amelia; Suheryanto Suheryanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2017)
The objective of the present study was to analyze the metal content of copper and lead in Enhalus accoroides seagrass in Batam Island waters. Samples of seagrass (E. accoroides) were collected from six locations along the western region of Batam Island then dried and performed with acid destruction. The measurements of Cu and Pb in the samples were conducted by Atomic Absorption Spectrophotometer. The result showed that there was an increasing of copper and lead contaminant level on sample E accoroides during two periods in a year. The Cu level ranged from 0.63 to 46.1 mg/kg, meanwhile, lead level ranged from 2.14 to 10.52mg/kg respectively. The highest accumulation of copper and lead were recorded on leaves, it was reached 10.81 mg/kg and 5.98mg/kg, respectively.Penelitian ini bertujuan menganalisis kandungan logam tembaga (Cu) dan timbal (Pb) pada lamun Enhalus accoroides di sepanjang perairan barat Pulau Batam. Sampel lamun dikumpulkan dari enam lokasi kemudian dikeringkan dan dilakukan destruksi dengan asam. Penentuan kadar logam tembaga dan timbal dalam sampel dilakukan dengan spektrometri serapan atom. Hasil penelitian menunjukan adanya peningkatan kadar logam Cu dan Pb pada sampel lamun E. accoroides selama 2 periode sampling dalam 1 tahun. Kadar logam Cu dan Pb pada lamun secara berturut berada pada rentang 0.63-46.1 mg/kg dan 2.14-10.52mg/kg. Akumulasi logam Cu dan Pb dalam lamun E. accoroides tertinggi pada bagian daun sebanyak 10.81 mg/kg Cu dan 5.98 mg/kg Pb.